POLA PEMUKIMAN KOTA SIGLI - Mirsa, Rinaldi (Arsitekno, 2013)
Sigli, the capital of Pidie region at Nanggroe Aceh Darussalam province, situated on East Sumatera Broadway, on Malaka Strait side precisely, connecting the cities amongst Banda Aceh to Medan, strategic also as the capital province hinterland –which its growth was influented by history. Morphology studied aims to searching for beginning of Sigli organism, so that the existing meanings should be comprehensive by integrated with historical perspective back-ground. The research reveals that, around the evolutions, Sigli has fan shaped cities spatial expressed –which natural obstruction at north side by Malaka Strait so that the growth inclined to other directions. Its point out the Sigli embryo -in periodical growth- be an organism and take the evolution so forth, which classified in three periods, include Poli/Pedir Empire Period (1413-1873), Colonial Period (1874-1954) and Safety Period (1955 untill now). The classify to seem the comprehensive typological and morphological physical elements of urban form which categories; dominated functions (commercial, government, settlement and religy), building characters (style, age, block and infrastructure) and placement at territory of Sigli. Such research inventions are best described into the following sentences: 1) the function was transformed, it shows by evolution physical elements of Sigli about each periods; 2) typological of Sigli urban spatial is function and spatial physical units, evolved by specific character of dominant elements; 3) by morphological, the pattern of Sigli urban spatial forced by government and natural topography; 4) the affected factors is the geographic, transportation and functions as traditional trading city, spreading of Islam and Colonial resisted. The research recommends that next morphology study should explored the typology of Sigli urban form to future implementations.